2018
DOI: 10.1021/acs.est.8b04102
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cellulose Nanocrystals (CNCs) into the Polyamide Layer of Thin-Film Composite (TFC) Nanofiltration Membranes for Enhanced Separation Performance and Antifouling Properties

Abstract: To achieve greater separation performance and antifouling properties in a thin-film composite (TFC) nanofiltration membrane, cellulose nanocrystals (CNCs) were incorporated into the polyamide layer of a TFC membrane for the first time. The results of Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy (XPS) confirmed the successful formation of the CNC-polyamide composite layer. Surface characterization results revealed differences in the morphologies of the CNC-TFC membranes compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(85 citation statements)
references
References 57 publications
1
84
0
Order By: Relevance
“…[54] Rejection of Na 2 SO 4 and MgSO 4 by the CNC-TFC membranes was similar to that observed for the CNC-TFC-0 membrane, at values of ≈98.7% and 98.8%, respectively. [54] Incorporation of ≈11 nm SiO 2 nanoparticles [15] and 3-aminopropyltriethoxysilane functionalized mesoporous silica nanoparticles [13] in the polypiperazine-amide separation layer has successfully shown the improvement in the separation properties of TFN NF membranes. A significant increase in water permeance with a compromised rejection of Na 2 SO 4 was achieved when only 0.03 wt% of functionalized mesoporous silica nanoparticles were incorporated within the separation layer.…”
Section: Introductionsupporting
confidence: 74%
“…[54] Rejection of Na 2 SO 4 and MgSO 4 by the CNC-TFC membranes was similar to that observed for the CNC-TFC-0 membrane, at values of ≈98.7% and 98.8%, respectively. [54] Incorporation of ≈11 nm SiO 2 nanoparticles [15] and 3-aminopropyltriethoxysilane functionalized mesoporous silica nanoparticles [13] in the polypiperazine-amide separation layer has successfully shown the improvement in the separation properties of TFN NF membranes. A significant increase in water permeance with a compromised rejection of Na 2 SO 4 was achieved when only 0.03 wt% of functionalized mesoporous silica nanoparticles were incorporated within the separation layer.…”
Section: Introductionsupporting
confidence: 74%
“…Additionally, the CMCs could increase the miscibility of MPD aqueous solution with TMC organic solution; as a result the MPD could diffuse faster and the membrane would form differently [28]. Finally, the shape of the crystals could contribute to the membrane’s morphological shape [22]. Figure 2i,h show 1.2% CMCs membrane after carving a rectangular piece of the top layer to illustrate the support layer structure following the thin film membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Antifouling property experiments toward 300 ppm bovine serum albumin solution indicated that the 0.1% CNCs membrane decreased the fouling by 11% compared to the virgin membrane. Bai et al [22] reported that filling 0.02 wt.% CNCs in the polyamide layer increased the water flux by 60%, with maintaining the Na 2 SO 4 and MgSO 4 salts rejection around 98.7 and 98.8%, respectively. NaCl rejection increased by increasing CNCs until it reached 22.7% at 0.02% loading.…”
Section: Introductionmentioning
confidence: 99%
“…The XPS spectrum of C 1s could be resolved into 3 peaks at 287.8, 285.8, and 284.6 eV, which were attributed to C]O, C-N or C-O, and C-C, respectively. 27,28 The N 1s spectrum could be tted to two peaks at 399.9 and 399.3 eV which were assigned to C-N in PIP monomer and N-C]O in polyamide, respectively indicating the polyamide selective layer successfully formed. The O spectrum could be tted to 3 peaks at 531.7, 531.3, and 530.5 eV, respectively.…”
Section: Characterization Of Uio-66-nh 2 and Uio-66-nh 2 -Pcmentioning
confidence: 97%